2023
DOI: 10.1186/s13568-023-01510-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic and transcriptome analysis of Bacillus velezensis CL-4 fermented corn germ meal

Abstract: Bacillus, an excellent organic-degrading agent, can degrade lignocellulose. Notably, some B. velezensis strains encode lignocellulases. However, their ability to degrade lignocellulose in fermented feed is not much appreciated. This study performed a comparative genomic analysis of twenty-three B. velezensis strains to find common carbohydrate-active enzymes (CAZymes) encoding genes and evaluated their potential to degrade lignocellulose. The comparative genomic and CAZyme database-based analyses identified se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 59 publications
(70 reference statements)
1
5
0
Order By: Relevance
“…Similarly, we sequenced the whole genome of B. velezensis BV-10 and found that B. velezensis BV-10 has numerous genes encoding cellulose-, hemicellulose-, and lignin-degrading enzymes in the CAZy database, including β-glucosidase, xylanase, laccase, and amylase. These results were similar to the findings of Chen et al [20]. Common genes from the GH1, GH3, GH4, GH5 and GH16 families participate in cellulose degradation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similarly, we sequenced the whole genome of B. velezensis BV-10 and found that B. velezensis BV-10 has numerous genes encoding cellulose-, hemicellulose-, and lignin-degrading enzymes in the CAZy database, including β-glucosidase, xylanase, laccase, and amylase. These results were similar to the findings of Chen et al [20]. Common genes from the GH1, GH3, GH4, GH5 and GH16 families participate in cellulose degradation.…”
Section: Discussionsupporting
confidence: 92%
“…At least one bacterial species of the genus Bacillus, Bacillus velezensis (B. velezensis), can degrade crude fiber, degrade cellulose into reducing sugars, increase soluble carbohydrates, and improve the fermentation substrate content [19]. B. velezensis may not be able to directly hydrolyze cellobiose because it lacks exocellulase, limiting its cellulose-degrading activity; thus, it is necessary to add appropriate exogenous enzymes for synergistic treatment [20]. To the best of our knowledge, no studies adding B. velezensis to silage in combination with other additives have been conducted to date.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the architecture of the active site of SIase places them within the glycoside hydrolase family, family 13 (GH13) [61]. Established in the early 1990s, the GH13 family [62] represents the largest family of polysaccharide metabolizing enzymes [63,64], grouping enzymes with hydrolytic [65], transferase [66,67], and isomerase activities [68]. Specifically, differences in substrate specificity and/or enzymatic activities among the GH13 family members led to its subdivision into subfamilies.…”
Section: Sucrose Isomerases Structure and Reaction Mechanismmentioning
confidence: 99%
“…In addition, B. velezensis fermentation signi cantly improved the overall nutritional level of CGM. Furthermore, the study of differential metabolites and differentially expressed genes during the B. velezensis fermentation showed that CAZymes enzyme genes mainly involved the degradation of cellulose, starch, pectin, and hemicellulose were signi cantly upregulated (Chen et al 2023). However, from the results of comparative genomics, enzyme activity assays, and cellulose degradation rate of fermented CGM, we found that B. velezensis lacks cellulase and cannot directly hydrolyze cellulose in CGM.…”
Section: Introductionmentioning
confidence: 99%